Inventory of Montane Zone Weeds in the Selo Tourism Area, Boyolali Regency, Central Java - Permatasari, Nila; Santhyami, S (Universitas Muhammadiyah Surakarta, 2023)
The weed is a plant that develops in undesirable areas and harms surrounding plants. Nonetheless, this herb can be used as a source of organic material, as a soil coating to prevent erosion, and as a traditional medicine. Weed growth can vary depending on the weed’s characteristics and environmental conditions. The Selo region is a verdant tourist destination in the montane zone's highlands. The land clearing caused a change in the area's vegetation. This study seeks to determine the Montane zone's weed vegetation varieties, composition, and structure. It is also connected to the release of land in Selo as a tourist area. This form of research is conducted at three different altitudes (1.600m asl, 1.700m asl, dan 1.800m asl). The intercept-point and exploration method is used, as well as data analysis involving the determination of summed dominance ratio (SDR) values and diversity index analysis. Consequently, there are variations in the composition and dominance of herbaceous vegetation at each height. There are 27 species of vegetation, with Imperata cylindrica (SDR 55.67% and 27.73% at 1.600m asl and 1.800m asl, respectively) dominating at 1.600m asl and 1.800m asl, and Ageratina riparia (SDR 20.86%) dominating at 1.700m asl. The highest diversity of grass species at the altitude of 1.800 m asl (H' 2,17). The highest sorensen’s similarity index is at altitudes of 1.600 m asl and 1.700 m asl (SSI 52,17%). The ecosystem conditions influenced by abiotic factors and the management of ecosystems impact the diversity and uniformity of grass species in the mountainous region of the Selo Tourist Area.